PRAKTEK PENGAMBILALIHAN TANAH OLEH PERUSAHAAN PERKEBUNAN KELAPA SAWIT DI KALIMANTAN BARAT â€œSTUDI KASUS PADA MASYARAKAT DAYAK IBAN DUSUN PAREH DESA SEMUNYING JAYA KECAMATAN JAGOI BABANG KABUPATEN BENGKAYANGâ€ - DUNASTA A.21211094, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2016)
ABSTRACTLand expropriation is apparently became quite serious discussion in the international community inline with the global food crisis that occurred in 2008. It immediately raises fears of country of its inability to meet the food for its own people. Realizing the impact of food scarcity would be bad for the life of a country. As a result, the